EXAMINING THE MODERATING ROLE OF INFORMATION AND COMMUNICATION TECHNOLOGIES BETWEEN RELATIONSHIP OF ORGANIZATIONAL CULTURE AND BUSINESS EXCELLENCE - Ali Alneyadi; Mohd Faiz Hilmi; Meor Azli Ayub; Anas Abudaqa, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
Organizational culture is inclusive of the norms of members within an organization. These are experienced by the individuals working within an organization and do describe the environment at an organization. The organizational culture norms regulate the behaviors of employees working within organization and also influence how the objectives are accomplished. In turn organizational culture results in business performance. Since businesses are affected by the rapidly happening changes in technology. Therefore, the study considered the role of information and communication technologies as a moderator between relationship of organizational culture and business excellence. The study followed the cluster sampling to select Dubai as a preferred place to conduct study and simple random sampling to collect data from respondents. The data were collected from the employees working in the public entities in Dubai, UAE. A total of 500 questionnaire were distributed among the employees, out which 350 questionnaires were returned and finally 338 valid questionnaires were used for data analysis. SPSS and PLS-SEM used for data analysis. The results of the study revealed that ICTs is a significant moderator between relationship of organizational culture (Empowerment, human resources orientation, improvement orientation, and interdepartmental coordination) and business excellence. Whereas results did not support the moderating role of ICTs between relationship of external orientation and business excellence. Overall the study has accomplished majority of the objectives. The results of the study can be utilized by managers of organizations to refine their cultural orientation which can boost their business excellence. The findings of the study can potentially prove to be economically beneficial for organizations.